Pengaruh Pelaksanaan Program Bela Negara terhadap Tingkat Aktivitas Fisik Anggota Resimen Mahasiswa pada PTN-BH Bandung: Studi Ex-Post Facto - Alfiani, Salma Nur; Supriyadi, Tedi; Alif, Muhammad Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to understand the contribution of the national defense program to the level of physical activity of members of the Student Regiment. The research method used in this research is Quantitative Descriptive with an Ex-Post Facto Study design; this research method is used to find out and analyze events that have occurred previously. This research uses an instrument in the form of an International Physical Activity Questionnaire Short Form (IPAQ-SF) questionnaire in Indonesian, which is distributed to the sample to obtain the required data. The sample in this research consisted of 36 UKM Student Regiment students at 3 State Universities with Legal Entities (PTN-BH) in Bandung. The sampling technique used is a simple random sampling technique. The t-test results obtained with a significant value (2-tailed) were (0.000). So the considerable value (2-tailed) is 0.000 <0.05, so Ha is accepted. The conclusion is that the national defense program positively influences increasing the level of physical activity of members of the Student Regiment. Keywords: Ex-Post Facto, IPAQ, National defense, Physical activity, Student Regiment